Toskańskie reformy kościelne na synodzie w Pistoi w 1786 roku - Kwiecień, Marcin (Czasopismo Prawno-Historyczne, 2010)
The Synod of Pistoia was the central point of the Tuscan reforms that aimed to regulate the relations between the State and the Church under the reign of Peter Leopold, the great duke of Tuscany 1765-1790. The wide reform programme supported by the bishops of Prato and Pistoia, and headed by Bishop Scipione de Ricci, encountered huge opposition of those who wanted to protect the old Roman Catholic Church order. The reformers went further and demanded fundamental changes in the theological doctrine, the liturgy and the organisation of church structures (the 57 point programme). Their claims incorporated some demands made by the Jansenists clergy. Some of those demands (missa dialogata, the use of the vernacular in the liturgy, or removal of Baroque influences from the Church) were far ahead their times, and some were recognised only later, and implemented by the Second Vatican Council. Although the Synod of Pistoia approved the reformers' postulates, they failed to be implemented throughout the whole of Tuscany and the new Synod-accepted legislation came to a spectacular end.